Myofibrillar Structural Variability Underlies Contractile Function in Stem Cell-Derived Cardiomyocytes - Ufford, Kathryn (Stem Cell Reports, 2021)
Disease modeling and pharmaceutical testing using cardiomyocytes derived from induced pluripotent stem cells (iPSC-CMs) requires accurate assessment of contractile function. Micropatterning iPSC-CMs on elastic substrates controls cell shape and alignment to enable contractile studies, but determinants of intrinsic variability in this system have been incompletely characterized. The objective of this study was to determine the impact of myofibrillar structure on contractile function in iPSC-CMs. Automated analysis of micropatterned iPSC-CMs labeled with a cell-permeant F-actin dye revealed that myofibrillar abundance is widely variable among iPSC-CMs and strongly correlates with contractile function. This variability is not reduced by subcloning from single iPSCs and is independent of the iPSC-CM purification method. Controlling for myofibrillar structure reduces false-positive findings related to batch effect and improves sensitivity for pharmacologic testing and disease modeling. This analysis provides compelling evidence that myofibrillar structure should be assessed concurrently in studies investigating contractile function in iPSC-CMs.